2007
DOI: 10.1038/nn2029
|View full text |Cite
|
Sign up to set email alerts
|

On and off domains of geniculate afferents in cat primary visual cortex

Abstract: On- and off-center geniculate afferents form two major channels of visual processing that are thought to converge in the primary visual cortex. However, humans with severely reduced on responses can have normal visual acuity when tested in a white background, which indicates that off channels can function relatively independently from on channels under certain conditions. Consistent with this functional independence of channels, we demonstrate here that on- and off-center geniculate afferents segregate in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
214
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(253 citation statements)
references
References 50 publications
28
214
3
Order By: Relevance
“…Surprisingly, although most textbooks assume that ON and OFF visual responses are balanced throughout the visual system, recent studies have identified a pronounced overrepresentation of the OFF visual responses in primary visual cortex (area V1) (1)(2)(3). This recent discovery resonates with pioneering studies by Galilei (4) and von Helmholtz (5) who noticed that visual spatial resolution was higher for dark than light stimuli.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Surprisingly, although most textbooks assume that ON and OFF visual responses are balanced throughout the visual system, recent studies have identified a pronounced overrepresentation of the OFF visual responses in primary visual cortex (area V1) (1)(2)(3). This recent discovery resonates with pioneering studies by Galilei (4) and von Helmholtz (5) who noticed that visual spatial resolution was higher for dark than light stimuli.…”
mentioning
confidence: 69%
“…Details of the surgical procedures have been described previously (3,37). All procedures were performed in accordance to the guidelines of the US Department of Agriculture and approved by the Institutional Animal Care and Use Committee at the State University of New York, State College of Optometry.…”
Section: Methodsmentioning
confidence: 99%
“…Several groups have studied V1 laminar variation (5,8,9,25,(47)(48)(49) by using spike-field coherence analysis (25), current source density analysis (5,49,50), or the BOLD signal in functional MRI (47). In this study, we used drifting gratings with spatial frequency equal to two cycles per degree, which are optimal stimuli for stimulating neurons in the V1 network (20,51).…”
Section: Dynamics Of γ-Band Power At Different Cortical Depths In V1mentioning
confidence: 99%
“…Psychophysical studies and measurements of visually evoked potentials show greater sensitivity to light decrements and dark spots in images (1,2). Also, more cortical cells respond to negative than positive contrasts (3). In fact, this asymmetry begins with the second order (bipolar) neurons in the retina, which rectify the local contrast signal from the cone array (Fig.…”
mentioning
confidence: 97%